ONE-STEP GROWTH CURVE OF WESTERN EQUINE ENCEPHALOMYELITIS VIRUS ON CHICKEN EMBRYO CELLS GROWN IN VITRO AND ANALYSIS OF VIRUS YIELDS FROM SINGLE CELLS - Dulbecco, R. (The Rockefeller University Press, 1954)
The rate of adsorption of WEE virus onto chicken embryo cells in vitro was determined both on a cell layer and on a cell suspension. One-step growth curves were determined in cell suspensions and on cell layers. The latent period varied between 2 and 3½ hours; it was shorter on cell layers and decreased with higher multiplicity of infection. The shortest period is probably the real latent period. The growth curves of the virus showed an initial exponential rise and reached a maximal constant value after 6 to 8 hours. The maximum virus yield per cell varied between 200 and 1000 on the cell layer, and between 100 and 200 in suspended cells. The yield of single infected cells was determined. An analysis of the distributions of the individual yields obtained after various periods of virus growth led to two main conclusions: (1) that virus is released from the same cell over a long period of time; (2) that one phase of the intracellular virus growth is exponential.